2021
DOI: 10.1111/1759-7714.14211
|View full text |Cite|
|
Sign up to set email alerts
|

The promoter hypermethylation of SULT2B1 accelerates esophagus tumorigenesis via downregulated PER1

Abstract: Background: Esophageal cancer is currently the eighth most common tumor in the world and a leading cause of cancer death. SULT2B1 plays crucial roles in tumorigenesis. The purpose of this study is to explore the role of SULT2B1 in esophageal squamous cell carcinoma (ESCC). Methods: The expression of SULT2B1 and its clinicopathological characteristics were evaluated in ESCC cohorts. Bisulfite genomic sequencing and methylation specific PCR were used to detect the promoter hypermethylation of the SULT2B1 gene. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…This affects the ability of DNA to coil around histones and results in a condensed heterochromatin conformation, which prevents genes from being transcribed [ 148 ]. High promoter methylation of ESCC suppressor genes, such as p16 [ 149 ], RASSF5A [ 150 ], SULT2B1 [ 151 ], SEMA3B [ 152 ], PTPN6 [ 153 ] and Bin1 [ 154 ] can lead to tumor suppressor gene silencing and cancer cell activation and can be used as a predictor of clinical outcome after radical resection in ESCC patients. Aberrant DNA methylation contributes to the development of radioresistance during anticancer therapy; for example, high methylation of death-associated protein kinase (DAPK) [ 155 ], CHFR [ 156 ] and FGF5 [ 157 ] is associated with a diminished response to CRT in ESCC, in which DNA methyltransferases (DNMTs) play an important role, including DNMT1, DNMT3A and DNMT3B.…”
Section: Reversal Strategy Of Escc Radioresistancementioning
confidence: 99%
“…This affects the ability of DNA to coil around histones and results in a condensed heterochromatin conformation, which prevents genes from being transcribed [ 148 ]. High promoter methylation of ESCC suppressor genes, such as p16 [ 149 ], RASSF5A [ 150 ], SULT2B1 [ 151 ], SEMA3B [ 152 ], PTPN6 [ 153 ] and Bin1 [ 154 ] can lead to tumor suppressor gene silencing and cancer cell activation and can be used as a predictor of clinical outcome after radical resection in ESCC patients. Aberrant DNA methylation contributes to the development of radioresistance during anticancer therapy; for example, high methylation of death-associated protein kinase (DAPK) [ 155 ], CHFR [ 156 ] and FGF5 [ 157 ] is associated with a diminished response to CRT in ESCC, in which DNA methyltransferases (DNMTs) play an important role, including DNMT1, DNMT3A and DNMT3B.…”
Section: Reversal Strategy Of Escc Radioresistancementioning
confidence: 99%
“…Increasing evidence shows that DNA methylation is closely related to the occurrence and development of cancers [ 11 ]. CpG islands are located in the promoter region and transcriptional initiation site of the gene, which are prone to DNA methylation and change the expression of oncogenes and tumor suppressor genes [ 12 ]. In the development of cancer, the methylation of specific gene promoter is considered to be a predictor of radiosensitivity and a prognostic factor.…”
Section: Epigenetics In Cancer Occurrence and Cancer Radiotherapymentioning
confidence: 99%
“…The increase in UHRF1 in cervical cancer (CC) tissue promotes the hypermethylation of the TXNIP promoter to downregulate the expression of TXNIP, thus promoting carcinogenesis ( Figure 2 a) [ 18 ]. SULT2B1 can inhibit the proliferation of esophageal squamous cell carcinoma (ESCC) cells, and the hypermethylation of its promoter can promote the progression of esophageal tumor by downregulating PER1 ( Figure 2 a) [ 12 ].…”
Section: Epigenetics In Cancer Occurrence and Cancer Radiotherapymentioning
confidence: 99%
“…In the process of sulfate conjugation, sulfotransferase enzymes are crucial participants, facilitating the conjugation of hormones, neurotransmitters, drugs and xenobiotic compounds 20 . SULT2B1, a member of the sulfotransferase family, also referred to as sulfotransferase family 2B member 1, has been associated with the progression of multiple cancer types, including prostate cancer, 21 gastric cancer 22 and oesophagus cancer 23 . Recent research has suggested that high expression of SULT2B1 could potentially accelerate the progression of liver cancer by impacting the tumour microenvironment 24 .…”
Section: Introductionmentioning
confidence: 99%
“… 20 SULT2B1, a member of the sulfotransferase family, also referred to as sulfotransferase family 2B member 1, has been associated with the progression of multiple cancer types, including prostate cancer, 21 gastric cancer 22 and oesophagus cancer. 23 Recent research has suggested that high expression of SULT2B1 could potentially accelerate the progression of liver cancer by impacting the tumour microenvironment. 24 Nevertheless, the effect of SULT2B1‐mediated lipid metabolism on the progression of CC remains unclear.…”
Section: Introductionmentioning
confidence: 99%